Current knowledge of prenatal diagnosis of mosaic autosomal trisomy in amniocytes: karyotype/phenotype correlations. (23rd June 2015) - Wallerstein, Robert; Misra, Sonya; Dugar, R. Bryce; Alem, Monika; Mazzoni, Ronit; Garabedian, Matthew J.
Abstract Genetic counseling for prenatal diagnosis of autosomal trisomy is complex because of the uncertainty of outcome, which is important for management decisions. Compilation of cases of prenatally diagnosed autosomal trisomies in amniocytes has been done previously in an attempt to elucidate the clinical phenotype of these pregnancies. It has been greater than a decade since these studies were completed. To update this work, we reviewed cases reported in the literature since that time. These cases are correlated with the prior reports to increase knowledge about outcomes and to hopefully improve the data available for genetic counseling. The risk of abnormal outcome can be summarized as: very high risk (>60%) for 47, +2/46; 47, +9/46; 47, +16/46; 47, +20/46; and 47, +22/46; high risk (40–59%) for 47, +5/46; 47, +14/46; and 47, +15/46; moderately high risk (20–39%) for 47, +7/46 47, +12/46; and 47, +17/46; moderate risk (up to 19%) for 47, +6/46 and 47, +8/46, and none were low risk. 47, +6/46 was originally indeterminate, 47, +7/46 was originally moderate risk, 47, +9/46 was originally high risk, and 47, +17/46 was originally low risk. © 2015 John Wiley & Sons, Ltd.